The Presence of Human Immunodeficiency Virus Type 1 Vpr Correlates with a Decrease in the Frequency of Mutations in a Plasmid Shuttle Vector - Jowett, Jeremy B. (American Society for Microbiology, 1999)
The human immunodeficiency virus type 1 (HIV-1) Vpr protein induces cell cycle arrest at the border of G(2) and M similar to the arrest caused by agents which damage DNA. We determined whether the presence of Vpr would affect the ability of cells to repair DNA. We developed a shuttle vector system to analyze the effect of Vpr upon the repair of UV-damaged DNA. Our results demonstrated that the presence of Vpr decreased the rate of deletions in this system. Of note, cells arrested in G(2) by other genotoxic agents also increased the frequency of DNA repair of UV-damaged shuttle vectors. We did not observe any direct effect of Vpr upon the rate of double-strand break repair and/or nucleotide excision repair of genomic DNA in cells. Our results suggest a role for HIV-1 Vpr in altering the frequency of DNA repair, a property which may have importance for HIV-1 replication and pathogenesis.